2017
DOI: 10.22159/ijpps.2017v9i3.16182
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Unani Anxiolytics (Somina) on General Reproductive Performance and Teratology in Rats

Abstract: Objective: Somina (herbal medicine) is used in Pakistan as Unani anxiolytics. It is composed of five medicinal plants. The current work was designed to evaluate the general reproductive and teratogenic effects of somina in two consecutive generations of rats according to the OECD guideline.Methods: Fertility study (a two-phase study) was done in Sprague-Dawley rats. 1st part: three groups' female rats (10 rats each group) received different doses orally. First group: The control group (saline), a single oral h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Further, the cardiovascular activity of somina showed its hypotensive effect [3], positive inotropic and negative chronotropic effects [4]. Despite the scientific activities and significant effects of Somina, some of the single dose toxicological studies showed that somina is practically non-toxic [5], and did not produce any teratological effect [6]. However, these alternative herbal medicines have a risk of toxicity for human [7].…”
Section: Lagenaria Vulgaris 12%mentioning
confidence: 99%
“…Further, the cardiovascular activity of somina showed its hypotensive effect [3], positive inotropic and negative chronotropic effects [4]. Despite the scientific activities and significant effects of Somina, some of the single dose toxicological studies showed that somina is practically non-toxic [5], and did not produce any teratological effect [6]. However, these alternative herbal medicines have a risk of toxicity for human [7].…”
Section: Lagenaria Vulgaris 12%mentioning
confidence: 99%
“…abnormalities which can be seen macroscopically. Fetal abnormalities were observed by looking at all external parts of the fetus from the head to the extremities using a surgical microscope [13][14][15][16].…”
Section: Research Articlementioning
confidence: 99%